Answer:
f(-1) = -4
Step-by-step explanation:
f(-1) simply means that what is f(x) when x = -1?
Just plug in -1 for <em>x</em> to find your answer:
f(-1) = -3(-1) + 2(-1) - 5
f(-1) = 3 - 2 - 5
f(-1) = 1 - 5
f(-1) = -4
Since this polynomial has 4 terms, factoring by grouping should be the first thing we try here.
So, we have:
![8x^2(3x-8)-7(3x-8)=0 \implies\\ (8x^2-7)(3x-8)=0](https://tex.z-dn.net/?f=%208x%5E2%283x-8%29-7%283x-8%29%3D0%20%5Cimplies%5C%5C%20%288x%5E2-7%29%283x-8%29%3D0%20)
So, we can use ZPP to find out roots:
![3x-8 =0 \implies\\ x=\frac{8}{3}\\ 8x^2-7=0 \implies \\ 8x^2=7 \implies \\ x^2=\frac{7}{8} \implies \\ x=\pm\frac{\sqrt{7}}{\sqrt{{8}}}\\ \text{Rationalizing denominator:}\\ x=\pm\frac{\sqrt{56}}{8}](https://tex.z-dn.net/?f=%203x-8%20%3D0%20%5Cimplies%5C%5C%20x%3D%5Cfrac%7B8%7D%7B3%7D%5C%5C%208x%5E2-7%3D0%20%5Cimplies%20%5C%5C%208x%5E2%3D7%20%5Cimplies%20%5C%5C%20x%5E2%3D%5Cfrac%7B7%7D%7B8%7D%20%5Cimplies%20%5C%5C%20x%3D%5Cpm%5Cfrac%7B%5Csqrt%7B7%7D%7D%7B%5Csqrt%7B%7B8%7D%7D%7D%5C%5C%20%5Ctext%7BRationalizing%20denominator%3A%7D%5C%5C%20x%3D%5Cpm%5Cfrac%7B%5Csqrt%7B56%7D%7D%7B8%7D%20)
So our three roots are:
![x \in \{\frac{8}{3},\frac{\sqrt{56}}{8},-\frac{\sqrt{56}}{8}\}](https://tex.z-dn.net/?f=%20x%20%5Cin%20%5C%7B%5Cfrac%7B8%7D%7B3%7D%2C%5Cfrac%7B%5Csqrt%7B56%7D%7D%7B8%7D%2C-%5Cfrac%7B%5Csqrt%7B56%7D%7D%7B8%7D%5C%7D%20)
1st add 7 to both sides : 3z = 21, 2nd divide both sides with 3: z = 7